Edukasi Manfaat Minyak Ikan Sebagai Upaya Pencegahan Stunting Masyarakat Desa Kuripan Kabupaten Lombok Barat, Nusa Tenggara Barat: (Education on the Benefits of Fish Oil as an Effort to Prevent Stunting in the Community of Kuripan Village Lombok Barat, Nusa Tenggara Barat) - Murniati; Dedy Suhendra; Erin Ryantin Gunawan; Dhony Hermanto; Sri Seno Handayani; Alya Hadranita Utami; Baiq Anggi Yustika Leni; Amida Rischia Ulfa (AL HAYAT: Jurnal Pengabdian Masyarakat, 2024)
Stunting is an important problem currently facing Indonesia. The prevalence rate of stunting is still in the high category when compared with WHO standards. NTB Province is one of the areas accelerating stunting reduction, including Kuripan District, West Lombok. Nutrition education programs for mothers are very important to tackle the problem of stunting. Nutrients play an important role in children's growth and development, such as fatty acids. Fatty acids are very good to consume for intelligence, so they can reduce stunting rates. One source of fatty acids is fish oil. The aim of this PkM activity is to provide education to mothers about stunting and how to prevent it, as well as the benefits of fish oil as a nutrient that plays an important role in efforts to prevent stunting. This series of PkM activities are direct outreach activities to the community, in this case the object of the PkM activity is the women reciting the TPQ Miftahul Ulum recitation in Kuripan Village, followed by the activity of distributing fish oil and installing educational posters about stunting and fish oil. The PkM activities ran smoothly and the mothers were very enthusiastic and eager to take part in the PkM activities. This activity provides a comprehensive understanding of stunting and the role of fish oil as an effective solution to prevent and overcome the problem of stunting in society